A series of modified mordenite for green fuel production from oleic acid - Nugrahaningtyas, Khoirina Dwi; Mukhsin, Sofia Aulia; Lukitawati, Rizki; Rahmawati, Fitria; Nurcahyo, I F; Kusrini, Eny; Hidayat, Yuniawan (Penerbit Universiti Kebangsaan Malaysia, 2025)
Green diesel and biogasoline are low-oxygen compounds in green fuel. Palm oil is a potential source of green fuel production through a hydrodeoxygenation reaction assisted by a specific catalyst. In this research, a series of transition metal (i.e., Fe, Co, Ni, Cu, and Zn) deposited in mordenite (MOR) catalysts were investigated for the hydrodeoxygenation reaction. Oleic acid was used to represent palm oil. All catalysts can convert oleic acid into green fuel products, particularly straight-chain alkane hydrocarbons with low free oxygen content. The Co/MOR catalyst converted 98.82% of oleic acid with a 76% selectivity for green fuel. The performance of the catalyst in one period follows the Sabatier Principle for the catalyst rather than the periodic system of elements.